Las escuelas unidocentes rurales como organizaciones de cambio - Pérez, Iris (2002)
The article reveals that multi-grade instruction schools emerged during the 1970s as a product of historical circumstances: the need to reduce the number of teachers according to the number of students. This decision was applied without providing for the quality of the school services (such as infrastructure or instructional material). Based on these experiences, the author analyzes the commitment that the universities must make with school with only one teacher assuming the position. She concludes with a list of challenges that these schools should keep in mind so that they can contribute to the transformation of rural communities.